The 3-2-1 Reading Comprehension Strategy: Students’ Reading Comprehension Development and Students’ Perception - Z Zainurrahman; Sriyani Djabir (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2020)
The 3-2-1 reading comprehension strategy is a new strategy and the study on the strategy is still rare at least in 2019. This strategy presents in the right time when the teacher needs to apply new strategy in the reading classroom. This research was conducted as an attempt to improve the students’ reading comprehension. Designed as a non-observation classroom action research, this research involved 36 students in a junior high school. There were two tests administered in the classroom, the pre-intervention and the post-intervention test. The intervention is conducted by doing three sessions of reading comprehension practice with the 3-2-1 strategy. The comparison of means between the tests by using paired sample t-test showed that there is a significant difference between the means where the post-intervention test mean is significantly higher than the pre-intervention test mean. This implies that the 3-2-1 reading comprehension strategy can be a good consideration for reading teachers. The students mentioned that this strategy has positive impacts on their reading practice and result. However, it is also captured that this strategy is only suitable for reading short text. This opens opportunity to the next researchers to conduct research on the use of 3-2-1 reading comprehension strategy on reading longer text.